AMERICAN POPULAR MUSIC AS RITUAL: EXPLORING THE MEANING OF RELIGION IN INTERACTIONS BETWEEN TAYLOR SWIFT AND SWIFTIES - Hamidan, Ahdi Sakha (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
Music as a product of popular culture has a considerable influence on social life. Music is not only limited to entertainment but has become a form of cultural expression. This can be seen in the relationship between idols and fans that form certain patterns as seen in religious rituals. This article explores how popular music can function as a ritual that creates a special closeness through the interaction between Taylor Swift as an idol and Swifties as her fans. Through analysing the relationship between Taylor Swift and her fans during concerts, interactions on social media, and her music, this article shows how Swifties construct their collective identity and build a seemingly sacred relationship with Taylor Swift. Using a cultural approach, this research will look at the ways in which Swifties express and adopt Taylor Swift's music as part of a social ritual that includes their emotional side. Through this relationship, popular music can create its own space, and fans are not only seen as passive consumers, but they also play an active role in the formation of a strong identity and community.